An Investigation of the Relationship between Sleep and Depression and the Affecting Factors ın Older Individuals - Aslan, GÃ¼lpÄ±nar; SAVCI BAKAN, AyÅŸe Berivan (Advances in Nursing & Midwifery, 2023)
Introduction: Sleep is a physiological need that constitutes one-third of human life and is necessary for enabling individuals’ participation in daily life activities in a compatible and healthy way. Insufficient sleep or excessive sleep has been reported to be associated with many health problems such as depressive symptoms. The present study aims to examine the relationship between sleep and depression and the affecting factors in older individuals. Methods: The design of this study is descriptive. The study was carried out with individuals aged 65 and over who were registered in FHCs providing primary health care services between June and October 2021. The sample size was calculated as 307 individuals using the sampling method with an unknown target population (confidence interval 95%, the margin of error 5%, and response distribution 28%). The Socio-Demographic Characteristics Form, The Geriatric Depression Scale-Short Form, and the Richard-Campbell Sleep Questionnaire were utilized as the data collection tools. The questions were sent to the older people online via telephone. SPSS statistical package program was used to analyze the data. Descriptive statistics, the Mann-Whitney U test, the Kruskal Wallis test, and Spearman Correlation analysis were performed. Results: Sleep quality was found to be low in those who had pain in a way to affect sleep and who experienced stress, sorrow, or unhappiness (P<0.05). The Geriatric Depression Scale mean scores were significantly higher in those who did not exercise regularly, who were dependent in daily life activities, and who had pain at a level to affect sleep (P<0.01). A negative, statistically significant, and weak relationship was found between depression and sleep quality (P<0.01). Conclusions: This study found a negative, statistically significant, and weak relationship between depression and sleep quality. Community health nurses are recommended to consider older individuals as privileged groups within the scope of community mental health practices, determine the factors that could cause depression and insomnia, and take active roles in the implementation of the interventions to prevent these. Interventions could include teaching older individuals coping methods and providing them with support to practice these methods, enhancing symptom management in individuals who have a chronic disease, implementing practices to reduce pain, and organizing exercise programs appropriate to older individuals' conditions.